A review of the effect of various ions on the properties and the clinical applications of novel bioactive glasses in medicine and dentistry - Saqib Ali; Imran Farooq; Kefi Iqbal (Saudi Dental Journal)
Bioactive glass is a novel material that dissolves and forms a bond with bone when exposed to body fluids. Bioactive glasses are silicate-based, with calcium and phosphate in identical proportions to those of natural bone; therefore, they have high biocompatibility. Bioactive glasses have wide-ranging clinical applications, including the use as bone grafts, scaffolds, and coating materials for dental implants. This review will discuss the effects of ions on the various compositions of bioactive glasses, as well as the clinical applications of bioactive glasses in medicine and dentistry. Keywords: Bioactive glass, Ions, Clinical applications, Medicine, Dentistry